2015
DOI: 10.1039/c5cc02251g
|View full text |Cite
|
Sign up to set email alerts
|

High-performance sodium batteries with the 9,10-anthraquinone/CMK-3 cathode and an ether-based electrolyte

Abstract: We here report a much improved electrochemical performance of sodium batteries with the 9,10-anthraquinone (AQ) cathode encapsulated in CMK-3, an ether-based electrolyte of high-concentration CF3SO3Na (NaTFS) as a sodium salt in triethylene glycol dimethyl ether (TEGDME) solvent, and the Na anode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
98
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 26 publications
1
98
1
1
Order By: Relevance
“…The capacity fading of the battery was attributed to ac omplicated variety of factors, such as material pulverization and battery polarization. [19] Unexpectedly,N a 2 AQ26DS also exhibited very impressive rate performancei n1m NaPF 6 in DME, giving rise to capacity values of 122, 118, and 110mAh g À1 at current densities of 100, 200, and 500 mA g À1 ,r espectively (Figure 3c). Although the capacity decay is unavoidable, the capacity retention at the 300th cycle ( Figure 3b)r emained at 87 %o ft he peak capacity value and 92 %o fi ts theoretical value (130 mAh g À1 ).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The capacity fading of the battery was attributed to ac omplicated variety of factors, such as material pulverization and battery polarization. [19] Unexpectedly,N a 2 AQ26DS also exhibited very impressive rate performancei n1m NaPF 6 in DME, giving rise to capacity values of 122, 118, and 110mAh g À1 at current densities of 100, 200, and 500 mA g À1 ,r espectively (Figure 3c). Although the capacity decay is unavoidable, the capacity retention at the 300th cycle ( Figure 3b)r emained at 87 %o ft he peak capacity value and 92 %o fi ts theoretical value (130 mAh g À1 ).…”
mentioning
confidence: 90%
“…[19] Initially we intended to use 1 m NaClO 4 in DME but the results were still not good (Figure S1 b). [19] Initially we intended to use 1 m NaClO 4 in DME but the results were still not good (Figure S1 b).…”
mentioning
confidence: 99%
“…A strategy designed to tackle the dissolution phenomenon of quinones was given by Chen et al [41]. The highly soluble 9,10-anthraquinone 20 (Figure 11) was encapsulated in a nanostructured porous carbon, CMK-3, in a 1:1 mass ratio.…”
Section: Carbonyl Insertion Compoundsmentioning
confidence: 99%
“…Guo et al have studied the solubility of anthraquinone (AQ) in CF3SO3Na-tetraglyme electrolytes at salt concentrations of 1-4 M and found continuously reduced AQ dissolution with the increase of electrolyte concentration. [26] In addition, the viscosity of the electrolyte increased by an order of magnitude as the concentration increased from 1 to 4 M (Figure 3a). Both decreased material solubility and increased electrolyte viscosity contributed to longer cycle life: the most concentrated electrolyte, 4 M CF3SO3Na in tetraglyme, afforded the highest reversible specific capacity and capacity retention (Figure 3b).…”
Section: Highly Viscous and Concentrated Electrolytesmentioning
confidence: 97%
“…(b) Cyclability of AQ electrode in these electrolytes. [26] The electrolyte concentration-cell performance relationship can get less straightforward for other cell systems. In a study on AQ in LiTFSI-dioxolane/DME electrolytes, Zhang et al found that a middling concentration (2 M) gave the highest cycling stability.…”
Section: Highly Viscous and Concentrated Electrolytesmentioning
confidence: 99%